Tax Dispute Resolution Analysis On Promotional Cost Adjustments - Wisnu Listiadi; Dahlia Sari (UNIVED Press, 2026)
This study aims to analyze tax disputes related to promotional expenses in the calculation of Corporate Income Tax (PPh Badan), focusing on the causes of disputes and the treatment of promotional expenses that do not meet administrative requirements. A qualitative approach using case studies is employed, analyzing 94 tax court decisions related to promotional expenses in 2024. The research also includes interviews with officials from the Directorate General of Taxes (DJP) and taxpayers. The results show that the main factors causing disputes are differences in interpretation between the tax authorities and taxpayers regarding the substance of promotional expenses, as well as incomplete administrative documentation, such as nominative lists. Although the court prioritizes the substance of promotional expenses, administrative non-compliance remains a reason for fiscal correction. The study identifies the need for formalizing tax policies related to promotional expenses into stronger regulations to provide clearer legal certainty. Additionally, it is recommended that the DJP improve the tax administration system by allowing taxpayers to substantiate legitimate promotional expenses, even if administrative documents are incomplete. The study also suggests enhancing training for tax officials to better understand the characteristics of taxpayers' businesses and the importance of proper document management to reduce future tax disputes.